2021
DOI: 10.5588/pha.20.0083
|View full text |Cite
|
Sign up to set email alerts
|

Diverse clinical and social circumstances: developing patient-centred care for DR-TB patients in South Africa

Abstract: OBJECTIVE: To describe the medical, socio-economic and geographical profiles of patients with rifampicin-resistant TB (RR-TB) and the implications for the provision of patient-centred care.SETTING: Thirteen districts across three South African provinces.DESIGN: This descriptive study examined laboratory and healthcare facility records of 194 patients diagnosed with RR-TB in the third quarter of 2016.RESULTS: The median age was 35 years; 120/194 (62%) of patients were male. Previous TB treatment was documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Finally, in terms of clinical implications, improvements in PCC for TB patients may be especially useful in minimising rifampicin-resistant TB [ 35 ]. TB patients have complex and multi-faceted needs and challenges that include significant socio-economic and medical problems and require a nuanced approach [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in terms of clinical implications, improvements in PCC for TB patients may be especially useful in minimising rifampicin-resistant TB [ 35 ]. TB patients have complex and multi-faceted needs and challenges that include significant socio-economic and medical problems and require a nuanced approach [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in terms of clinical implications, improvements in PCC for TB patients may be especially useful in minimising rifampicin-resistant TB [ 35 ]. TB patients have complex and multi-faceted needs and challenges that include significant socio-economic and medical problems and require a nuanced approach [ 35 ]. Some studies have demonstrated that improvements in patient-health provider relationships can enhance health outcomes in patients with a wide variety of health problems [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Mburu et al 56 used HbA1c of > 6.0% as the cut-off for defining DM in Kenya. Among patients with DRTB, the pooled prevalence was also 7.0% (95% CI 2.0-12.0, I 2 = 97.6%, p < 0.001) [35][36][37]39,42,44,48,57 .…”
Section: Prevalence Of Dmmentioning
confidence: 97%
“…The prevalence of hypertension ranged from 0.3% in Mozambique 54 to 37.0% in South Africa 59 . The prevalence in DRTB was 13.0% (95% CI 4.0-22.0, I 2 = 97.3%, p < 0.001) in six studies 37,42,44,48,57,60 . East Africa had the highest pooled prevalence of hypertension at 22.0% (95% CI 12.0-33.0, I 2 = 96.5%, p < 0.001) followed by Southern Africa at 14.0% (95% CI 8.0-19.0, I 2 = 99.3%, p < 0.001) and West Africa at 6.0% (95% CI 1.0-11.0, I 2 = 94.4%, p < 0.001).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation